2004
DOI: 10.1002/jnr.20122
|View full text |Cite
|
Sign up to set email alerts
|

GAD67 and GAD65 mRNA and protein expression in cerebrocortical regions of elderly patients with schizophrenia

Abstract: Gamma-Aminobutyric acid (GABA), the principal inhibitory neurotransmitter of CNS, has been consistently implicated in the pathophysiology of schizophrenia. GABA is synthesized from glutamate by the enzyme glutamic acid decarboxylase (GAD). Two isoforms of GAD have been identified and have been named GAD65 and GAD67 based on their apparent molecular weights. In this study, GAD65 and GAD67 mRNA and protein levels were measured by using real-time RT-PCR and immunoblotting, respectively, in post-mortem brain tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 71 publications
5
53
0
Order By: Relevance
“…The amount of GABA and [1,2-13 C]GABA from [1,2-13 C]acetate remained unchanged, whereas, [2-13 C]GABA was decreased in the CRFC in the present study. Thus, GABA turnover from [1-13 C]glucose was affected, which corroborates recent reports of impaired activity of glutamic acid decarboxylase (GAD) in schizophrenic patients (Guidotti et al, 2000;Volk et al, 2000;Dracheva et al, 2004). In this context, it is noteworthy that a decrease in GAD 67 has been suggested as a link between the glutamatergic and dopaminergic theories of psychosis (Hossein Fatemi et al, 2005).…”
Section: Effects Of Repeated Mk801 On Metabolism D Kondziella Et Alsupporting
confidence: 88%
“…The amount of GABA and [1,2-13 C]GABA from [1,2-13 C]acetate remained unchanged, whereas, [2-13 C]GABA was decreased in the CRFC in the present study. Thus, GABA turnover from [1-13 C]glucose was affected, which corroborates recent reports of impaired activity of glutamic acid decarboxylase (GAD) in schizophrenic patients (Guidotti et al, 2000;Volk et al, 2000;Dracheva et al, 2004). In this context, it is noteworthy that a decrease in GAD 67 has been suggested as a link between the glutamatergic and dopaminergic theories of psychosis (Hossein Fatemi et al, 2005).…”
Section: Effects Of Repeated Mk801 On Metabolism D Kondziella Et Alsupporting
confidence: 88%
“…Decreased GAD67 is one of the most highly replicated postmortem findings in patients with schizophrenia (Akbarian et al, 1995;Guidotti et al, 2000;Dracheva et al, 2004;Fatemi et al, 2005). Although levels of full-length KCC2 mRNA expression are not significantly altered in the DLPFC in schizophrenia, the levels of the truncated transcript of KCC2 AK098371 are reduced.…”
Section: Ak098371 and Rs3749034mentioning
confidence: 91%
“…Moreover, decreased GAD65 as well as GAD67 mRNA expression in prefrontal and other neocortical association areas of schizophrenics has been reported in different studies that used postmortem tissue from different brain banks [70] . Studies have also reported increased GAD67 mRNA and protein levels in prefrontal and primary sensory (visual) cortices of elderly schizophrenia subjects [71] . Since a reduction of GABAergic neurons results in a loss of the key modulatory inhibition of the pyramidal and interneuron processes, which may mediate the central executive function of working memory in schizophrenia subjects, several studies have looked at the effect of GABAergic agents in the treatment of schizophrenia [72][73] .…”
Section: Bdnf and Gabaergic System In Schizophreniamentioning
confidence: 99%